PENGGUNAAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING MENINGKATKAN KETERAMPILAN PASSING BOLA BASKET PADA MATA PELAJARAN PENJAS ORKES KELAS IX MTS NEGERI 1 KOTA SERANG - Ahpudin (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2021)
This research was conducted in class IX G MTs Negeri 1 Kota Serang with 28 students, nine male students, and 19 female students in the 1st semester of the 2015-2016 academic year. The stages are planning, implementing, observing, and reflecting in each cycle, and this research was completed in two cycles. The research data obtained through observations by researchers is data on the results of learning the skills of passing big ball games obtained through performance from the psychomotor domain. Data analysis in this study used descriptive analysis using percentage techniques to see trends that occur in learning activities. This study aims to determine the effectiveness of the Contextual Teaching and Learning learning model in improving basketball passing skills in the IX class of Penjas Orkes subjects at MTs Negeri 1 Kota Serang semester 1 of the 2015-2016 academic year. Based on the results of this study, it can be concluded that the Contextual Teaching and Learning learning model can improve basketball passing skills in the IX class of Penjas Orkes subjects at MTs Negeri 1 Kota Serang in the 2015-2016 academic year, where learning outcomes in the initial conditions are 67.86% or 19 students, at the end of the first cycle it became 78.57% or 22 students. Atat the end of the second cycle, it became 92.86% or 26 students.